ChemInform Abstract: Structural Properties of the Acidification Products of Scandium Hydroxy Chloride Hydrate. Issue 8 (February 2016) - Boyle, Timothy J.; Sears, Jeremiah M.; Neville, Michael L.; Alam, Todd M.; Young, Victor G. Jr.
Abstract: The reaction of Sc with conc.